Impact of Digital Marketing, Service Quality, and Product Innovation on Skintific TikTok Shop Consumers - Dian Ferriswara; Susi Susanti; Sarwani Sarwani; Liling Listyawati (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2025)
This study explores the influence of digital marketing, service quality, and product innovation on customer satisfaction among Skintific skincare consumers on TikTok Shop. Employing a quantitative, explanatory research design, the study used purposive sampling to collect 200 valid responses from consumers who had purchased Skintific products via TikTok Shop. Data were collected through an online questionnaire and analyzed using multiple linear regression with SPSS, preceded by validity, reliability, and classical assumption tests. The results revealed that product innovation had the most significant impact on customer satisfaction (β = 0.589, p < 0.001), followed by service quality (β = 0.343, p < 0.001). However, digital marketing did not have a significant direct effect on customer satisfaction (β = 0.019, p = 0.746). The model explained 86.9% of the variance in customer satisfaction (R² = 0.869), indicating strong combined effects from the three factors. These findings suggest that post-purchase factors, particularly product innovation and service quality, are more decisive in influencing customer satisfaction than promotional efforts alone. Managerial implications highlight the importance of continuous product development, enhancing service responsiveness and reliability, and integrating digital marketing with value delivery to optimize customer satisfaction. The study contributes to social commerce literature by clarifying the distinct roles of marketing, service quality, and innovation in the context of TikTok Shop, providing both theoretical insights and practical guidance for brand strategy in social commerce platforms. This research adds to the understanding of how businesses can strategically leverage product innovation and service excellence to enhance consumer satisfaction and foster long-term customer loyalty in the competitive social commerce landscape.